2019
DOI: 10.1103/physrevb.99.165123
|View full text |Cite
|
Sign up to set email alerts
|

Generalized transfer matrix states from artificial neural networks

Abstract: Identifying variational wave functions that efficiently parametrize the physically relevant states in the exponentially large Hilbert space is one of the key tasks towards solving the quantum manybody problem. Powerful tools in this context such as tensor network states have recently been complemented by states derived from artificial neural networks (ANNs). Here, we propose and investigate a new family of quantum states, coined generalized transfer matrix states (GTMS), which bridges between the two mentioned… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 58 publications
(114 reference statements)
0
24
0
Order By: Relevance
“…ANNs are very powerful tools that have been used for numerous applications such as medicine [34][35][36][37], transportation [23,[38][39][40][41], optimization [31,[42][43][44][45], and even quantum physics [46][47][48][49][50] among others.…”
Section: Artificial Neural Network (Ann)mentioning
confidence: 99%
“…ANNs are very powerful tools that have been used for numerous applications such as medicine [34][35][36][37], transportation [23,[38][39][40][41], optimization [31,[42][43][44][45], and even quantum physics [46][47][48][49][50] among others.…”
Section: Artificial Neural Network (Ann)mentioning
confidence: 99%
“…The recent successes of artificial neural network techniques have entailed a large interest in applying them to quantum many-body systems, in particular as ansatz for the wavefunction of (strongly correlated) quantum systems [5,13,21,22]. Such neuralnetwork quantum states have the principal capability to describe systems hosting chiral topological phases [8,13,17], or to handle large entanglement [11,12,19].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the number of free parameters scales as O(N M ) for a fully connected RBM (where M is the number of hidden variables), while is O(N χ 2 ) for an MPS. Recently, a strong connection between NN and TN has been pointed out [40][41][42][43][44][45][46]: among others, it has been shown that the fully connected RBM can be explicitly rewritten as a MPS with an exponentially large auxiliary dimension, i.e. χ = 2 M (see Fig.…”
Section: Introductionmentioning
confidence: 99%